2017
DOI: 10.1371/journal.pone.0174646
|View full text |Cite
|
Sign up to set email alerts
|

Long-duration effect of multi-factor stresses on the cellular biochemistry, oil-yielding performance and morphology of Nannochloropsis oculata

Abstract: Microalga Nannochloropsis oculata is a promising alternative feedstock for biodiesel. Elevating its oil-yielding capacity is conducive to cost-saving biodiesel production. However, the regulatory processes of multi-factor collaborative stresses (MFCS) on the oil-yielding performance of N. oculata are unclear. The duration effects of MFCS (high irradiation, nitrogen deficiency and elevated iron supplementation) on N. oculata were investigated in an 18-d batch culture. Despite the reduction in cell division, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 50 publications
(77 reference statements)
1
3
0
1
Order By: Relevance
“…In particular, the proportion (% total FA, Table 2) of 16:0 increased, as well as that of 18:1n 9 , which suggests that they played a conspicuous role in the course of TAG reserve. Almost all of our results are similar to the findings of [43] for the fatty acid profile of N. oculata under stressed conditions (high irradiation, nitrogen deficiency, and elevated iron supplementation). They reported that, under stressed conditions, the SFA and MUFA proportions increased accordingly, with their sum increasing from 63.56% to 92.18%.…”
Section: Effects Of Sbae On Fatty Acid Profile Of N Oculatasupporting
confidence: 89%
“…In particular, the proportion (% total FA, Table 2) of 16:0 increased, as well as that of 18:1n 9 , which suggests that they played a conspicuous role in the course of TAG reserve. Almost all of our results are similar to the findings of [43] for the fatty acid profile of N. oculata under stressed conditions (high irradiation, nitrogen deficiency, and elevated iron supplementation). They reported that, under stressed conditions, the SFA and MUFA proportions increased accordingly, with their sum increasing from 63.56% to 92.18%.…”
Section: Effects Of Sbae On Fatty Acid Profile Of N Oculatasupporting
confidence: 89%
“…The percentage of neutral lipids gradually increased for both wild-type and M1 mutant strain and reached the highest (35 and 27%, respectively) on day 12. Nutrient limitation is known to induce TAG accumulation as a stress response, and a previous study showed that C16:0 reached the maximum of around 40% of TFA under these conditions ( Wei and Huang, 2017 ). In order to further investigate the increase in EPA content, two time-points were chosen based on the FAs profiles between TAG and EPA, EPA percentages, and absolute EPA quantifications.…”
Section: Resultsmentioning
confidence: 98%
“…Además, los lípidos en la microalga Np se concentran en pocas gotas La Tabla 7 muestra que, para Np, los porcentajes de lípidos neutros (F4) y lípidos polares (F3) son aproximadamente 37 y 3%. Al comparar estos resultados con los de Y. Ma y colaboradores [16], en estudios realizados de tres cepas de microalgas Nannochloropsis oceanica, en condiciones controladas de laboratorio, cuyos resultados de lípidos neutros y polares fueron 23-32 y 21-26%, respectivamente, puede inferirse que la microalga Np estudiada ha sufrido estrés por las condiciones de cultivo en el invernadero, pues incrementaron sus niveles de lípidos neutros y disminuyeron los niveles de lípidos polares, efecto similar al reportado por Wei y su equipo [17].…”
Section: Resultados Y Discusiónunclassified